José Luis Martínez y Christopher Domínguez Michael, La literatura mexicana del siglo XX. Pres. de R. Tovar y de Teresa. C.N.C.A., México, 1995; 283 pp. - Díaz Arciniega, Víctor (El Colegio de México, 1996)
Se reseñó el libro: La literatura mexicana del siglo XX.